The Effect of WhatsApp-Based PAI Learning Management on The Active Involfement of PAI Students - Iis Marsithah; Nanda Ulfia Chair; Syauqiyah Salsabilla; Reva Khairani; Dea Amira (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid digital transformation in education has prompted the integration of communication platforms like WhatsApp into learning management, particularly in Islamic Religious Education (PAI) programs. This qualitative case study examines the influence of WhatsApp-based PAI learning management on student active engagement at UIN Ar-Raniry, involving three PAI lecturers and three 2024 cohort students as participants. Data were collected through semi-structured interviews, observations, and document analysis, analyzed interactively via Miles and Huberman's model (data reduction, display, and verification). Findings reveal WhatsApp excels as a supplementary tool for administrative management, facilitating schedule sharing, pre-class material distribution (H-1), task coordination, attendance tracking, and documentation enhancing behavioral engagement in routine tasks. However, it falls short in fostering deep academic, emotional, and social engagement. Academic involvement remains superficial, limited to brief responses rather than conceptual mastery of PAI content; emotional disengagement arises from text-based rigidity, monotony, and lack of visual cues, eroding motivation; social interactions feel awkward due to formality concerns and one-way communication. Technical issues (e.g., unstable networks) and non-technical barriers (e.g., distraction, AI misuse) further hinder effectiveness. Ultimately, WhatsApp-based management positively impacts administrative engagement but inadequately supports profound PAI comprehension and pedagogical skill-building, underscoring its role as a bridge rather than a primary platform. Recommendations advocate hybrid models blending WhatsApp with face-to-face interactions for optimal PAI learning outcomes.